Dignose og behandling i en nepalesisk landsby - Poulsen, Hans-Christian Køie (Tidsskriftet Antropologi, 2019)
According to statistics, the health of the Nepalese population has improved. This progress is described by the authorised health sector as a result of its efforts. It is just as likely that self-medication with bio-medical drugs could have had a quite substantial effect. Though the rural population today willingly integrates bio-medical drugs into their sickness related practice, it does not necessary lead to adjustment of their hitherto held beliefs and practices. On the contrary, the new medicine is used very much in accordance with the already existing ideas. For the rural population most illness cases have their course beyond the frame of reference normally accepted within Western natural science discourse. The majority of illness cases is thought to be caused by the influence of various invisible harmful agents. It is thus not surprising that the villagers mainly direct their attention towards these. The treatment of physical symptoms is usually considered to be of lesser importance.